Electrostatic control and the need of feedback control ionization in critical environment of MEMS manufacturing process - Chakkaew, Anusorn; Titiroongruang, Wisut (My University, 2010)
This paper describes new electrostatic control countermeasures and solutions for critical electrostatic control environment for MEMS manufacturing processes, especially in MEMS's wafer handling that needs low electrostatic voltage. This includes personnel grounding methodology, ESD event measurement, and low ion imbalance ionization to support current and future needs of the MEMS. © (2010) Trans Tech Publications.
Keywords: Electrostatic discharge; ESD event; HBM; MEMS; Personal grounding